THE CHARACTERISTICS OF AUDIT COMMITTEE, AUDIT QUALITY AND PROFIT MANAGEMENT IN NON-FINANCIAL SECTOR COMPANIES - Osianto, Vira; Pudjolaksono, Drs. Eko (jfpublisher, 2022)
One of the main things that often attract the attention of users of financial statements in assessing the company's performance is to look at the company's profits for that period. This encourages managers to show the best performance for their interests, so it is not uncommon for managers to practice earnings management. With the auditing of financial statements carried out by the audit committee and external auditors, it is hoped that they can detect and prevent those manipulation. The purpose of this study is to provide empirical evidence regarding the effect of audit committee characteristics and audit quality on earnings management. The data used in this study are non-financial sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period which were selected using the purposive sampling method. The hypotheses were tested using multiple linear regression models. The results showed that audit committee size, audit committee expertise, the size of the Public Accounting Firm (KAP) and firm size had a significant effect on earnings management.